2022
DOI: 10.3390/nu14245228
|View full text |Cite
|
Sign up to set email alerts
|

Association between Sarcopenia and Nutritional Status in Chilean Older People Aged 65 Years and Older

Abstract: In 2018 the European Working Group on Sarcopenia in Older People (EWGSOP2) updated the definition of sarcopenia, with loss of muscle strength being the primary feature. The objective is to describe and associate sarcopenia and nutritional status in a group of Chilean older adults aged 65 years and older. Methods: Descriptive, associative and comparative study, with a cross-sectional design and a quanti-qualitative approach. A number of 155 institutionalized and community-dwelling Chilean older people aged 65 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 24 publications
2
3
0
Order By: Relevance
“…However, compared to the results of the nutritional screening tool (53.6%), the incidence of malnutrition in care institutions measured by BMI is significantly lower, which is similar to the results of the study by Crovetto Mattassi et al. (2022). At the same time, the researchers believe that it must be emphasised that malnutrition must be distinguished from underweight, as it can also occur in obese individuals, and that a low BMI can be the result of a person's previous weight loss (Billeret et al., 2023; Wolters et al., 2019).…”
Section: Discussionsupporting
confidence: 87%
“…However, compared to the results of the nutritional screening tool (53.6%), the incidence of malnutrition in care institutions measured by BMI is significantly lower, which is similar to the results of the study by Crovetto Mattassi et al. (2022). At the same time, the researchers believe that it must be emphasised that malnutrition must be distinguished from underweight, as it can also occur in obese individuals, and that a low BMI can be the result of a person's previous weight loss (Billeret et al., 2023; Wolters et al., 2019).…”
Section: Discussionsupporting
confidence: 87%
“…Similarly, an analysis from the Brazilian Longitudinal Study of Ageing (ELSI-Brazil) showed that BMI was inversely associated with muscle weakness measured by hand grip strength [ 19 ]. In contrast, others report an increased risk of sarcopenia/probable sarcopenia in older adults with obesity [ 20 ]. A further consideration is that the loss of muscle mass in aging is frequently offset by increases in fat mass, meaning that BMI may therefore remain unchanged [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…A notable methodological difference was their use of the mean of six handgrip attempts (both hands), in contrast to our use of the maximum value of three trials with dominant hand. When examining the Chilean studies [ 31 33 ], some adapted their handgrip strength cut-offs to better fit their specific study cohorts. Applying these tailored cut-offs to our sample resulted in a higher prevalence of probable sarcopenia than those reported in the Chilean studies.…”
Section: Resultsmentioning
confidence: 99%